2014
DOI: 10.1186/1756-0500-7-696
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection in sheep and goats slaughtered for human consumption in Central Ethiopia

Abstract: BackgroundToxoplasmosis is one of the most common parasitic zoonoses worldwide. Humans get infections with T. gondii after ingesting raw or undercooked meat or oocysts via contaminated soil, food or water; or congenitally by transplacental transmission of tachyzoites. The objectives of the present study were to estimate the seroprevalence and assess risk factors for T. gondii infection in sheep and goats slaughtered for human consumption in Central Ethiopia.MethodsA cross-sectional study was carried out from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 32 publications
5
33
1
2
Order By: Relevance
“…The highest prevalence of infection (19.09%) was detected in two-year-old or older animals, followed by intermediate prevalence (12.67%) in the 1–2 year age group, while the prevalence found in animals in the ≤1 year age group was 6.50% (Table 2). These results are similar to those of previous investigations [17, 20, 41, 42], suggesting the possibility of horizontal transmission in the investigated herds.…”
Section: Resultssupporting
confidence: 92%
“…The highest prevalence of infection (19.09%) was detected in two-year-old or older animals, followed by intermediate prevalence (12.67%) in the 1–2 year age group, while the prevalence found in animals in the ≤1 year age group was 6.50% (Table 2). These results are similar to those of previous investigations [17, 20, 41, 42], suggesting the possibility of horizontal transmission in the investigated herds.…”
Section: Resultssupporting
confidence: 92%
“…In fact, according to Dubey and Kirkbride (1989), most of sheep acquire the infection before the age of 4 years; however, only one third of the older females remain seronegative in heavily contaminated farms. As well, we found no significant difference between sexes; a similar observation was reported by Khezri et al (2012) and Gebremedhin et al (2014), unlike Clementino et al (2007) who reported a higher seroprevalence in females. The antibody titers obtained are higher as compared to cattle, with a maximum titer of 1:2048; a similar titer was reported by Rossi et al (2011) and higher titers reaching 1:65536 were reported by Garcia et al (1999).…”
Section: Discussionsupporting
confidence: 88%
“…Production system, breed and purpose of keeping small ruminants (for meat and milk) are as described previously [17, 18]. In this study, sheep and goats aged over six months were sampled.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was undertaken from September, 2011 to June, 2013 using hearts of 91 DAT seropositive animals (47 sheep and 44 goats) and 14 seronegative animals (10 sheep and 4 goats) from previous seroepidemiological study [18]. …”
Section: Methodsmentioning
confidence: 99%